Evolution of the Distribution and Dynamic of Microplastic in Water and Biota: A Study Case From the Gulf of Gabes (Southern Mediterranean Sea) - Ben Ismail, Sana; Costa, Elisa; Jaziri, Hela; Morgana, Silvia; Boukthir, Moncef; Ben Ismail, Mohamed Anis; Minetti, Roberta; Montarsolo, Alessio; Narizzano, Riccardo; Sammari, Cherif; Faimali, Marco; Garaventa, Francesca (Frontiers in Marine Science, 2022)
Marine plastic pollution represents a major problem owing to its increasing presence in the environment, persistence and ability to spread in every compartment in the form of small plastic particles, namely microplastics (MPs). Studies concerning MPs abundance in the Mediterranean Sea are growing, but their occurrence in the Southern regions remains largely unexplored. In this study, distribution, abundance, size, and polymer type of microplastics were investigated in surface water samples collected with a Manta net (200 μm mesh size) and in 118 marine specimens of commercial interests, including fishes, crustaceans, and mollusks, during Spring and Autumn 2019 EU H2020 Claim Project sampling Campaigns in the Gulf of Gabes (Southern Mediterranean Sea). Laboratory characterization showed significant plastic pollution concentrations, with an average abundance of 312,887 and 77,110 items/km2 in surface water samples collected in Spring and Autumn, respectively. A 3D hydrodynamic and Tracking Model was used to identify dispersal and transport pathways of the floating plastics, reporting a seasonal variability observed in MPs distribution between I (Spring) and II Campaign (Autumn). Despite the high values of MPs abundance found in surface water samples, an overall low frequency of ingestion among studied species was observed, with a maximum value of 20% of individuals (in Scomber scombrus) found with ingested MPs. The present study contributes to expand our state of knowledge regarding MPs pollution level in water and biota samples collected in the Gulf of Gabes, an area of particular interest for its biological resources, but still little investigated.